2012
DOI: 10.1139/f2012-111
|View full text |Cite
|
Sign up to set email alerts
|

Does large-scale ocean circulation structure life history connectivity in Antarctic toothfish (Dissostichus mawsoni)?

Abstract: A multidisciplinary approach incorporating otolith chemistry, age data, and numerical Lagrangian particle simulations indicated a single, self-recruiting population of Antarctic toothfish (Dissostichus mawsoni) in the Southeast Pacific Basin (SPB) and Ross Sea, with a life history structured by the large-scale circulation. Chemistry deposited prior to capture along otolith edges demonstrated strong environmental heterogeneity, yet the chemistry in otolith nuclei, deposited during early life, showed no differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 43 publications
(54 reference statements)
4
62
0
Order By: Relevance
“…The centers are located over Pennell Bank (C2 in Figure b; Figure b for topographical names), Ross Bank (C3), and under the western half of the RIS (C4). The zonal flows along the north‐south running troughs agree with schematic views of currents over the shelf in Ashford et al () and Smith et al (), which are based on the ROMS model of Dinniman et al () with resolutions comparable to the RSSM. Mean transports of C2, C3, and C4 are 1.0, 1.4, and 1.1 Sv, respectively.…”
Section: Results and Discussion: Circulation And Water Masses In The supporting
confidence: 83%
See 1 more Smart Citation
“…The centers are located over Pennell Bank (C2 in Figure b; Figure b for topographical names), Ross Bank (C3), and under the western half of the RIS (C4). The zonal flows along the north‐south running troughs agree with schematic views of currents over the shelf in Ashford et al () and Smith et al (), which are based on the ROMS model of Dinniman et al () with resolutions comparable to the RSSM. Mean transports of C2, C3, and C4 are 1.0, 1.4, and 1.1 Sv, respectively.…”
Section: Results and Discussion: Circulation And Water Masses In The supporting
confidence: 83%
“…Understanding the advection of these water masses toward the RIS, which is separated from the shelf break by several hundred kilometers of shallower continental shelf (mean depth of ∼530 m), is a crucial aspect in assessing the future RIS stability in the advent of a warming climate. Although some circulation features of the Ross Sea continental shelf are known (Ashford et al, ; Carter et al, ; Dinniman et al, ; W. O. Smith et al, ; Smith et al, ), understanding the seasonal variability is hampered due to the lack of wintertime data. Under the interior of the RIS, few oceanographic measurements exist to date (Jacobs et al, ), hence the specific patterns of ocean currents in the cavity can only be inferred from numerical models.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-adult male SESs may also benefit from this by feeding on the shelf or slope regions without being constrained by sea ice. They likely feed on the most abundant pelagic finfish in Antarctic shelf water, the Antarctic silverfish (Pleuragramma antarcticum), from surface to ~900m (Daneri and Carlini, 2002;La Mesa et al, 2010) or on epibenthic Antarctic toothfish (Dissostichus mawsoni) Smith et al, 2007) with juvenile finfish principally found on the shelf while adults are found along the slope (Ashford et al, 2012) sometimes shallower than though within ~1000 m of the water column (Watwood et al, 2006) or under fast ice in mid-depths (12-180 m; Fuiman et al 2002). Shallow dives observed in high sea ice concentration close to the Antarctic coast (10 ± 6% of the total dives for males) could correspond to specific foraging activity associated with the rich under-ice community of fish and invertebrates (Ainley et al, 1991).…”
Section: Male Foraging Behaviour In the Piz And Fizmentioning
confidence: 99%
“…Another species of particular note is the Antarctic toothfish (Dissostichus mawsoni), which is a large species with a maximum length greater than 2 m, weights over 200 kg, and is the target of a commercial fishery Ashford et al, 2012aAshford et al, , 2012b. Biochemical analyses and model studies have suggested regional ocean circulation facilitates the movement of adult Antarctic toothfish along the shelf slope into the banks and ridges of the Pacific-Antarctic Ridge where they spawn; their pelagic eggs and early life stages are transported in the flow back into the coastal regions of the Ross Sea (Ashford et al, 2012a;Hanchet et al, 2015).…”
Section: Impacts Of Advection On Fish Populations In the Antarcticmentioning
confidence: 99%
“…Biochemical analyses and model studies have suggested regional ocean circulation facilitates the movement of adult Antarctic toothfish along the shelf slope into the banks and ridges of the Pacific-Antarctic Ridge where they spawn; their pelagic eggs and early life stages are transported in the flow back into the coastal regions of the Ross Sea (Ashford et al, 2012a;Hanchet et al, 2015). The ecological importance of mesopelagic species, and particularly myctophids, in Southern Ocean food webs is being increasingly recognized (Ainley et al, 1992;Pakhomov et al, 1996;Duhamel et al, 2000;Pusch et al, 2004;Collins et al, 2012).…”
Section: Impacts Of Advection On Fish Populations In the Antarcticmentioning
confidence: 99%